KUALITAS DAN TINGKAT PENCEMARAN AIR EMBUNG YEH KORI DI DESA JUNGUTAN, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM - Wayan Suryana; Ni Luh Gede Sudaryati; I Putu Sudiartawan (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2022)
Many people use surface water for their daily needs. Reservoir water in Yeh Kori Embung is used for various purposes; however, there has not been an inspection of the quality and pollution index that allows contamination of the reservoir. This study aims to evaluate the quality and level of pollution of Yeh Kori Embung Water in Jungutan Village, Karangasem Regency. A descriptive design with a mix-method approach was used in this study. Water samples were taken at five different stations for two periods. Furthermore, physical, chemical and biological examinations are carried out and adjusted to quality standards. The results show that pH (5.2 – 5.4) is in the acidic category and does not meet the requirements while temperature (25.3oC), TSS (32.02 mg/L), DO (6.56 mg/L), BOD ( 1.36 mg/L), COD (10.4 mg/L), NO3-N (4.38 mg/L), Total P (0.021 mg/L), and Fecal Coliform (75.08 MPN/100mL) meet quality requirements. The pollution index (IP=1.085) is classified as lightly polluted. Yeh Kori Embung water does not meet the requirements of class two water quality and requires periodic evaluation and inspection. Keywords: pH, Pollution level, Reservoir, Water quality, Yeh Kori.